Building resilience in teachers and students: A qualitative study - Tore Aune; Ottar Ness (Tidsskrift for Norsk Psykologforening)
This study aimed to explore teachers’ perceptions of and experiences with training in and implementation of the School Resilience Program (SRP). The results are grounded on a multistage focus group discussion. A thematic analysis approach was employed to identify and report patterns and themes. Three themes were identified: (1) the teachers’ experience of enhanced confidence and skills in addressing students’ emotional challenges after learning SRP; (2) the teachers found that learning SRP techniques expanded their professional development and personal advantages; and (3) the teachers’ discovered that training together as colleagues builds a unified language and strategy through collaborative training. Training in and implementation of SRP appeared to provide teachers with tools and interventions, as well as increased self-efficacy. According to the participants, training in the SRP protocol appeared to give them a greater sense of coherence. SRP is compatible with and applicable to Scandinavian school systems. Future studies should explore how teachers, and especially students, experience the SRP protocol, examine the circumstances under which the programme is most appropriate, and investigate its effectiveness.